Digital Transformation, Innovation Management and Entrepreneurial Culture at an Edutainment Startup Company in Uzbekistan - Yangiboeva Diyorakhon Shavkat; Muhamad Arief Ramdhany (The International Journal of Business Review (The Jobs Review), 2023)
This research aimed to investigate the Effect of Digital Transformation on Innovation Management and Entrepreneurial Culture at an Edutainment Startup Company in Uzbekistan. This research utilizes a quantitative approach and a questionnaire as the primary tool to collect data from 46 employees in that company. The collected data were analyzed through a comprehensive analysis of data using Partial Least Square (PLS). The results revealed a substantial and positive effect of Digital Transformation on Innovation Management and Entrepreneurial Culture. This impact was influenced not only by direct effects but also through the mediating roles of Innovation Management. The implications highlight the strategic importance of embracing digital transformation to enhance innovation management and entrepreneurial culture in the relevant sectors. This implies that organizations should view digital transformation as more than just an adoption of technology but as a strategic initiative that can shape the very culture and mindset of the company, driving innovation and entrepreneurship from within. The research adds valuable novelties to the growing bodyÂ